Medicare Managed Care Spillovers and Treatment Intensity. (11th May 2015) - Callison, Kevin
Summary: Evidence suggests that the share of Medicare managed care enrollees in a region affects the costs of treating traditional fee‐for‐service (FFS) Medicare beneficiaries; however, little is known about the mechanisms through which these 'spillover effects' operate. This paper examines the relationship between Medicare managed care penetration and treatment intensity for FFS enrollees hospitalized with a primary diagnosis of AMI. I find that increased Medicare managed care penetration is associated with a reduction in both the costs and the treatment intensity of FFS AMI patients. Specifically, as Medicare managed care penetration increases, FFS AMI patients are less likely to receive surgical reperfusion and mechanical ventilation and to experience an overall reduction in the number of inpatient procedures. Copyright © 2015 John Wiley & Sons, Ltd.